2016
DOI: 10.1371/journal.pone.0149600
|View full text |Cite
|
Sign up to set email alerts
|

CDDO-Me Redirects Activation of Breast Tumor Associated Macrophages

Abstract: Tumor-associated macrophages can account for up to 50% of the tumor mass in breast cancer patients and high TAM density is associated with poor clinical prognosis. Because TAMs enhance tumor growth, development, and metastatic potential, redirection of TAM activation may have significant therapeutic benefit. Our studies in primary human macrophages and murine breast TAMs suggest that the synthetic oleanane triterpenoid CDDO-methyl ester (CDDO-Me) reprograms the activation profile of TAMs from tumor-promoting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 62 publications
3
23
1
4
Order By: Relevance
“…2c, CDDO-Me treatment decreased MMP2 levels in TAMs. Moreover, CDDO-Me significantly attenuated expression of Arg1 in TAMs treated in vivo, as previously observed in vitro 12 . Increased levels of Arg1 are characteristic of alternatively activated macrophages and immunosuppressive TAMs.…”
Section: Cddo-me Confers Immunostimulatory Transcriptional Activationsupporting
confidence: 85%
See 1 more Smart Citation
“…2c, CDDO-Me treatment decreased MMP2 levels in TAMs. Moreover, CDDO-Me significantly attenuated expression of Arg1 in TAMs treated in vivo, as previously observed in vitro 12 . Increased levels of Arg1 are characteristic of alternatively activated macrophages and immunosuppressive TAMs.…”
Section: Cddo-me Confers Immunostimulatory Transcriptional Activationsupporting
confidence: 85%
“…In this regard, we recently demonstrated that the methyl ester of the synthetic triterpenoid 2-cyano-3,12-dixooleana- 1,9(11)dien-28-oic acid (CDDO-Me) repolarizes alternatively activated human macrophages and murine primary mammary TAMs from immunosuppressive to immunostimulatory 12 . CDDO-Me has been shown to strongly induce Nrf2 activation via Keap1 interaction and to upregulate anti-inflammatory and antioxidant pathways in cancer cells and cell lines 13,14 .…”
mentioning
confidence: 99%
“…In the experiments following an acute challenge with LPS (Figure 2), CDDO-Im suppressed levels of CCL2, which recruits monocytes to sites of inflammation, and VEGF, which promotes angiogenesis, in the pancreas. These findings mirror results we have obtained with the triterpenoid CDDO-Me; we have recently shown that CDDO-Me markedly attenuates CCL2 and VEGF expression in PyMT tumor associated macrophages both in vitro and in vivo (20). Elevated levels of both CCL2 (35), and VEGF (36) are poor prognostic indicators in patients with PDAC.…”
Section: Discussionsupporting
confidence: 84%
“…In this regard, our results suggest that CDDO-Im may enhance immune activation in PDAC by inhibiting immune-suppressive MDSC infiltration and by enhancing expression of T cellactivating cytokines, including IL-1β and TNFα (Supplementary Table 1, available at Carcinogenesis Online). Intriguingly, we have shown that CDDO-Me redirects activation of breast tumor associated macrophages from an M2 immune-suppressive to M1 immune-stimulatory phenotype (20). Although beyond the scope of the present study, our future work will determine whether CDDO-Im mediates similar effects on PDAC tumor associated macrophages.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation